2020
DOI: 10.1038/s41598-020-71338-7
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the relationship between air pollution and meteorological conditions in China under environmental governance

Abstract: Extensive studies have been carried out on the impact of human activities on air pollution, but systematic investigation on the relationship between air pollutant and meteorological conditions is still insufficient, especially in the context of China’s site scale and recent comprehensive environmental pollution control. Here, we used a spatial interpolation technology to establish a set of data sets of pollutants and meteorological elements that are spatially matched at 896 stations in China to reveal the air … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
99
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 174 publications
(114 citation statements)
references
References 51 publications
14
99
0
1
Order By: Relevance
“…Similarly, a significant negative correlation was also observed between wind speed and atmospheric pressure at lag-0 to 21. These results are found to be consistent with the results of other studies (Liu et al, 2020;Hoang and Tran, 2021).…”
Section: Correlation Between Covid-19 Cases Meteorological Variables and Air Pollutantssupporting
confidence: 93%
See 1 more Smart Citation
“…Similarly, a significant negative correlation was also observed between wind speed and atmospheric pressure at lag-0 to 21. These results are found to be consistent with the results of other studies (Liu et al, 2020;Hoang and Tran, 2021).…”
Section: Correlation Between Covid-19 Cases Meteorological Variables and Air Pollutantssupporting
confidence: 93%
“…In addition, associations among and between air pollutants and meteorological variables are presented in Table 4. It is apparent that meteorological conditions influence air pollutants' concentration over a particular region (Liu et al, 2020). In our study, NO2 showed a significant positive correlation with PM2.5 at lag-0 to 21 and a significant negative correlation with CO and O3 at lag-0.…”
Section: Correlation Between Covid-19 Cases Meteorological Variables and Air Pollutantssupporting
confidence: 43%
“…For NO 2 , in addition to temperature, atmospheric pressure has also been identified as one of the leading meteorological factors for changes in pollutant concentration in the eastern coastal and northeastern regions. Relative humidity also had a significant impact on NO 2 concentration in the Beijing-Tianjin-Hebei region (38). These results are consistent with previous studies (39,40).…”
Section: Discussionsupporting
confidence: 92%
“…Considering those cognizance along with the observations throughout the study, it may be opined that the complete lockdown with strict regulations could substantially decrease the pollution levels, and so the dissemination rate of COVID-19 too. The pre-eminence of weather parameters on air quality is indubitable and evinced globally (Bhaskar and Mehta, 2010;Fisher, 2002;Yansui Liu et al, 2020e;Panofsky and Prasad, 1967;Qin et al, 2020;Seo et al, 2018;Zhang et al, 2015), hence its signi cant association with COVID-19 dissemination during a year-long period over India has been certainly revealed through the present study. We also postulate that amelioration from this pandemic could be viable, preferably in a freshened (less polluted) environment with non-scorching weather conditions.…”
Section: Discussionmentioning
confidence: 54%